Does The Disclosure of Carbon Emissions and Green Investment Affect Corporate Financial Performance (A Case Study of The Mining and Energy Subsectors) - Rahmawati, Arifiyani Novita; Hartoko, Sri (Riset Akuntansi dan Keuangan Indonesia, 2025)
The purpose of the study is to provide empirical evidence on the influences of carbon emission disclosure (CED) and green investment (GI) on financial performance (FP), as well as the impact of GI on CED. The research population consisted of companies in the mining and energy subsectors listed on the Indonesia Stock Exchange for the period 2018–2019. The sample selection technique used purposive sampling with a total sample of 162 observations from 27 companies. This study examines the effects of CED and GI on FP before COVID-19, during COVID-19, and in the new normal and post-COVID-19 periods. The results indicate that before and during COVID-19, CED had a significant impact on FP, while GI had no effect. However, in the new normal and post-COVID-19 periods, neither CED nor GI influenced FP. Additionally, GI was found to have an impact on CED.